Desempenho de novilhos holandeses em pastagem de capim aruana suplementados com níveis de farelo de trigo - Lazzarotto, Eduardo Felipe Coleraus de Oliveira (2015)
The objective was to evaluate the performance of Holstein steers in aruana grass pasture (Panicum maximum) supplemented with wheat bran levels. The work was conducted at the Federal Technological University of Paraná, Campus Dois Vizinhos, in an area of 2,8 ha, divided into eight paddocks of 0,35 ha each. 16 steers with an average age of 11 months with an average weight of 230 kg, all castrated. The experimental design was completely randomized with four levels: 0; 0,4; 0,8 and 1,2% of body weight and two replications, using wheat bran as a supplement in aruana grass pasture. To determine the weight and average daily gain were weighed every 28 days. The forage mass is estimated at 28 days, by the double sampling method, with 20 visual samples and five samples cut close to the ground using squares of 1 m². These assessments were collected two sub-samples, one for the determination of dry matter and the other to evaluate the participation of the structural components of the pasture. The rate of daily herbage accumulation was evaluated using two exclusion cage grazing per paddock. In the pasture samples were evaluated the dry matter, crude protein, neutral detergent fiber, acid detergent fiber, ether extract and in vitro digestibility of dry matter. The first trial resulted in a weight gain per hectare five kilos more than the last period Supplementation with different wheat bran levels in power holstein steers in the growing phase did not influence animal performance characteristics, not even the productive characteristics of the pasture.